Tips for Building a Literacy Culture Among Islamic Religious Education Teachers - Kusnawan; Saepulah (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
The increasingly rapid development of the internet and technology has an impact on the lack of literacy culture in schools. Students spend more of their free time playing with cellphones or gadgets. Islamic religious education (PAI) teachers are an important milestone in developing the character and morals of students to become better. Building good character and morals can start by cultivating literacy in schools. This research aims to explore the role of Islamic Religious Education (PAI) Teachers in building a literacy culture in schools. PAI teachers have a strategic position in instilling religious and moral values ​​in students, as well as guiding them in understanding and practicing religious teachings. It is hoped that this research will be able to provide an impact and alternative solutions to the development of PAI teacher competency, especially in improving literacy culture in schools. This research uses a qualitative approach with the library research method